Knowledge Management Sebagai Upaya Pengembangan Learning Organization Di Lembaga Pendidikan Islam - Nuryana, Zalik (Universitas Alma Ata, 2017)
Being a superior education institution is the hope of every educational institution, not exception in Islamic education. In the midst of competition between these institutions, Islamic education should be able to respond to changes quickly if it does not want to displaced and dead. Each of Islamic educational institutions that have certain characteristics to be able to be the strength and foundation to become a superior institution. Knowlegde Management as an approach which is based on the understanding that the task of the school is a good understanding of how and when the creation of knowledge should be supported, how to use the accumulated knowledge that has been created so that this knowledge can improve productivity. With the knowledge of their respective Islamic educational institutions and managed properly expected of Islamic educational institutions remained firm stand to become an institution of superior and competitive.